Open versus arthroscopic approach in the treatment of femoroacetabular impingement: a case–control study with two-years follow up - Bruno Dutra Roos; Milton Valdomiro Roos; Antero Camisa Júnior; Ezequiel Moreno Ungaretti Lima; Maurício Domingos Betto (Revista Brasileira de Ortopedia)
Abstract Objective To compare clinical and imaging results and complications between patients treated for femoroacetabular impingement (FAI) who underwent either anterior open surgery or an arthroscopic approach, with a minimum follow-up of two years. Methods This retrospective case–control study included patients submitted to FAI surgical treatment between November 2007 and March 2012. Patients treated with open surgery were compared with those treated with arthroscopy. Patients were clinically assessed by the modified Harris Hip Score, Non-Arthritic Hip Score, and internal hip rotation. Patients were radiographically assessed by the center-edge angle, joint space width, alpha angle, neck-head index, degree of arthrosis, and presence of heterotopic ossification of the hip. Results In the study period, 56 patients (58 hips) with FAI were included; 16 underwent open surgery and 40 underwent arthroscopy. The 40 patients treated by the arthroscopic route had a mean follow-up of 29.1 months, and 75.6% presented good or excellent clinical results. The radiographic evaluation parameters progressed to normal levels. The 16 patients who underwent open surgery had a mean follow-up of 52 months, and 70.58% presented good or excellent clinical results. The radiographic evaluation parameters progressed to normal levels. Postoperative clinical and radiographic results were considered similar in both groups. Conclusions Arthroscopy and open surgery treatments for FAI provided comparable clinical and radiographic results. However, a higher rate of complications was observed in the open surgery group.